Effects of ashwagandha (Withania Somnifera) supplementation on body composition and blood health indices in professional wrestlers - Dlugolecka, B.; Jówko, E.; Kotowska, J.; Gierczuk, D. (Polish Journal of Sport and Tourism, 2023)
Introduction. The purpose of this randomized, double-blind, placebo-controlled study was to evaluate the effect of ashwagandha supplementation on the body composition, blood health and recovery indices, as well as the safety of ashwagandha supplementation in wrestling.